Elevated levels of aquaporin-4-containing extracellular vesicles in cerebrospinal fluid of patients with bipolar disorder - Lennart Wetterberg; Fariborz Mobarrez; Rolf Nybom; Håkan Wallén; Aurimantas Pelanis; Dietrich von Rosen; Mikael Landén (Upsala Journal of Medical Sciences, 2025)
Objectives: To examine a hypothetical dysfunction of the brain water channels in bipolar disorder by analyzing aquaporin-4 (AQP4) exposing extracellular vesicles (EVs) in cerebrospinal fluid (CSF) from individuals with bipolar disorder types 1 and 2, and healthy controls. Methods: We analyzed exposure of AQP4 EVs to three different epitopes – the N- and C-terminals, and the epitope containing amino acids 273–291 – in CSF by flow cytometry in 24 individuals with bipolar disorder (type 1, n = 20; type 2, n = 4) and in 14 healthy controls. Results: We observed significantly higher levels of EVs expressing AQP4 in the CSF from individuals with bipolar disorder compared with healthy controls. Specifically, the mean ± SD concentration of AQP4 + EVs per μl CSF for the N-terminal epitope was 346 ± 22 in patients with bipolar disorder type 1, 386 ± 78 in those with bipolar disorder type 2, compared with 39 ± 6.9 in the healthy control group (P < 0.0001). For AQP4+ EVs targeting the C-terminal epitope, the corresponding values were 350 ± 22 for bipolar disorder type 1, 374 ± 46 for bipolar disorder type 2, and 36 ± 6.3 for healthy controls. Similarly, EVs expressing AQP4+ epitopes containing amino acids 273–291 showed concentrations of 344 ± 17 in bipolar disorder type 1, 398 ± 63 in bipolar disorder type 2, and 38 ± 6.4 in the control group (P < 0.0001). Conclusion: Our findings revealed significantly more EVs expressing the three AQP4 epitopes in patients with bipolar disorder compared with healthy controls. This suggests a dysregulated expression of AQP4, implicating a potential disruption in brain water homeostasis as a contributing pathogenic mechanism in bipolar disorder.